Tailoring efficient materials for NPK all-in-one granular fertilization - Ribeiro, Caue; Giroto, Amanda S.; do Valle, Stella F.; Guimaraes, Gelton G.F.; Molina, Arthur; Reis, Heitor P.G. [UNESP]; Fernandes, Dirceu M. [UNESP]; Bernardi, Alberto C.C.; Mattoso, Luiz H.C. (American Chemical Society (ACS), 2020)
Food security is one of the biggest challenges for the next few decades, especially with the accelerated population growth rates. Therefore, achieving a better nutrient use efficiency is crucial to enhance crop yields and productivity, which depend directly on how macronutrients are supplied. It is notably complex because fertilizers are often applied as granules instead of more soluble powdered forms. Here, we propose a new model for an all-in-one NPK fertilizer production, which allows quickly adjustable compositions in multi-nutrient granules. Thus, thermoplastic starch has been used as a biodegradable matrix binder mixed with the fertilizers in a continuous process by extrusion. Urea and KCl were considered as N and K sources, respectively. P sources with different solubilities (triple superphosphate (TSP) and Bayovar and Patos phosphate rocks) have been tested and compared. The greenhouse experiment revealed that the TSP composite promoted superior biomass production than the standard application, in addition to an overall better nutrient uptake. While Bayovar did not benefit from the all-in-one granule, Patos results were improved in this system, revealing a boost in its solubilization.